The hidden role of heterotrophic bacteria in early carbonate diagenesis - Mónica Sánchez-Román; Viswasanthi Chandra; Sebastian Mulder; Camila Areias; John Reijmer; Volker Vahrenkamp (Scientific Reports)
Abstract Microbial impacts on early carbonate diagenesis, particularly the formation of Mg-carbonates at low temperatures, have long eluded scientists. Our breakthrough laboratory experiments with two species of halophilic aerobic bacteria and marine carbonate grains reveal that these bacteria created a distinctive protodolomite (disordered dolomite) rim around the grains. Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD) confirmed the protodolomite formation, while solid-state nuclear magnetic resonance (NMR) revealed bacterial interactions with carboxylated organic matter, such as extracellular polymeric substances (EPS). We observed a significant carbon isotope fractionation (average δ13C = 11.3‰) and notable changes in Mg/Ca ratios throughout the experiments. Initial medium δ13C was − 18‰, sterile sediments were at 2‰ (n = 12), bacterial-altered sediments were − 6.8‰ (n = 12), and final medium δ13C was − 4.7‰. These results highlight the role of bacteria in driving organic carbon sequestration into Mg-rich carbonates and demonstrate the utility of NMR as a tool for detecting microbial biosignatures. This has significant implications for understanding carbonate diagenesis (dissolution and reprecipitation), climate science, and extraterrestrial research.